Isolation and Determination of Antibacterial Sensitivity Characteristics of Staphylococcus aureus from Lactating Cows in West Shewa Zone, Ethiopia - Negassa Feyissa; Tesfaye Alemu; Dagim Jirata Birri; Asnake Desalegn; Melaku Sombo; Shubisa Abera (Veterinary Medicine International)
Staphylococcus (S.) aureus is one of the etiologies of bovine mastitis, hindering milk production and productivity in dairy farms. This study was aimed at assessing the distribution of bovine mastitis and the isolation rate of S. aureus in milked cows of West Shewa Zone. The clinical mastitis was diagnosed by physical methods including observation and palpation, whereas the subclinical mastitis was tested by the California mastitis test (CMT). All of the cows tested for mastitis were aseptically sampled (teat-milk) for bacteriology. The bacterium was primarily identified based on colony characterization, catalase, coagulase tests, and Gram stain reaction. Finally, MALDI-TOF Biotyper confirmed the species. The antibacterial sensitivity characteristics of the isolates to different antibacterial drugs were tested by the disk diffusion method. The drugs were selected based on the frequent usage in veterinary medicine in the study area. By using particular primers, the presence of the resistance (mecA and blaZ), and thermonuclease (nuc) genes were determined by polymerase chain reaction (PCR). The data were analyzed by R statistical software. The associations between the dependent variables (prevalence of mastitis and S. aureus) and the explanatory variables were analysed by chi-square (χ2) and logistic regression tests at a 95% confidence interval (CI). Accordingly, 258 lactating cows were examined, of which 97 (37.6%) were mastitis positive. Of these mastitis positive cows, 59 (60.8%) were subclinical and 38 (39.2%) were clinical. Among the 258 milk samples, 43 (16.7%) were positive for S. aureus. According to the results of the current investigation, subclinical mastitis was significantly more prevalent than clinical mastitis (p<0.05). The disease was found varied with the lactation stage of the animal, milking with washed hand, udder washing before milking, and tick infestation of the teat. In comparison to animals from farms with lower number of lactating cows, the prevalence of the bacteria was significantly higher in animals managed in farms with large (OR = 12.58, 95% CI = 2.33–68.54, and p<0.05) and medium (OR = 12.58, 95% CI = 2.33–68.54, and p<0.05) population of lactating cows per herd. The isoation rate of the bacterium was also found significantly higher in tick-infested cows (OR = 27.69, 95% CI = 9.71–93.01, and p<0.05) than tick free cows. The antibiogram tests revealed that the isolates resisted penicillin G and tetracycline group drugs (oxytetracycline and tetracycline). Moreover, the nuc gene was confirmed to be present in all of the examined isolates. However, they were not found harboring blaZ and mecA genes. We concluded that S. aureus is sustaining as a main causative agent of bovine mastitis, and they were resistant to the frequently used antibiotics in public and veterinary medicines in the study areas. Therefore, research-based interventions need to be taken in action to combat the pathogen.